The Importance of Local Wisdom Values of Customary Law in The Management of National Land Law - Saktiawan, Muhammad Dias; Wiranto, Agus Prasetia (Jurnal Daulat Hukum, 2025)
Agrarian conflicts between customary law communities and the government have recently begun to flare up, this is due to the government's lack of attention to communities that have been guaranteed in communal rights, conflicts that occur in the form of disputes and even criminalisation of communities whose rights are deprived without legal certainty. This research uses the juridical analysis method by making secondary data as the main data in the form of literature studies and laws related to agrarian issues. The importance of customary law local wisdom values in the management of national land law can be concluded that the integration of these values has a significant positive impact in maintaining the sustainability of natural resources, strengthening environmental protection, and preserving cultural wisdom in Indonesia. Through the recognition and implementation of local wisdom values, we can create harmony between customary law and national law, improve the welfare of local communities, and ensure that land management is carried out in a sustainable manner.